Structural and Predictive Equivalency of the Wisconsin Smoking Withdrawal Scale across Three Racial/Ethnic Groups - Castro, Yessenia (Oxford University Press, 2011)
INTRODUCTION: The Wisconsin Smoking Withdrawal Scale (WSWS) is a valid and reliable scale among non-Latino Whites but has not been validated for use among other racial/ethnic groups despite increasing use with these populations. The current study examined the structural invariance and predictive equivalency of the WSWS across three racial/ethnic groups. METHODS: The WSWS scores of 424 African American, Latino, and White smokers receiving smoking cessation treatment were analyzed in a series of factor analyses and multiple-group analyses. Additionally, hierarchical logistic regression analyses were conducted to determine whether WSWS scores differentially predicted smoking relapse across racial/ethnic groups. These analyses were consistent with a step-down hierarchical regression procedure for examination of test bias. RESULTS: The 7-factor structure of the WSWS was largely confirmed in the current study, with the exception of the removal of two offending items. Evidence of full invariance across race/ethnicity was found in multiple-group analyses. The WSWS total score and subscales measuring anger, anxiety, concentration, and sadness predicted relapse, whereas the hunger, craving, and sleep subscales did not. None of these scales displayed differential predictive ability across race/ethnicity. The WSWS sleep subscale showed a significant interaction with race/ethnicity such that it was a significant predictor of relapse among Whites but not African Americans or Latinos. CONCLUSIONS: Overall, the WSWS is similar in structure and predictive of relapse across racial/ethnic groups. Caution should be exercised when using the WSWS sleep subscale with African Americans and Latinos.